2006
DOI: 10.1097/01.ccm.0000208440.66756.c2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric in-intensive-care-unit cardiac arrest: Incidence, survival, and predictive factors*

Abstract: In-ICU cardiac arrest is associated with high in-hospital mortality and subsequent morbidity in survivors. Prearrest renal dysfunction and epinephrine infusion were associated with increased in-hospital mortality. The use of post-arrest ECMO within 24 hrs was associated with reduced mortality. Rigorous prospective evaluation of the role of ECMO following cardiac arrest is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(112 citation statements)
references
References 20 publications
3
99
0
10
Order By: Relevance
“…Several pediatric studies have shown increased mortality rates for patients cannulated after 30 minutes of conventional CPR. 7,11,28,34 However, other retrospective studies [8][9][10]12,20,26,27,29,31,32 of pediatric patients have shown positive outcomes with median CPR duration of 30 to 50 minutes. Even more interesting are the multiple case reports 24,27,30,32,37 of successful cannulation and survival to discharge in patients receiving CPR of up to 90 to 220 minutes.…”
Section: Population Of Patientsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several pediatric studies have shown increased mortality rates for patients cannulated after 30 minutes of conventional CPR. 7,11,28,34 However, other retrospective studies [8][9][10]12,20,26,27,29,31,32 of pediatric patients have shown positive outcomes with median CPR duration of 30 to 50 minutes. Even more interesting are the multiple case reports 24,27,30,32,37 of successful cannulation and survival to discharge in patients receiving CPR of up to 90 to 220 minutes.…”
Section: Population Of Patientsmentioning
confidence: 96%
“…However, survival statistics for ECPR are more encouraging, with a general rate of success of near 40% to 60%. [2][3][4][5][7][8][9][10][11][12][13][19][20][21][22][23][24][25][26] Multi-institutional data obtained in 2012 from the Extracorporeal Life Support Organization (ELSO), an international registry and database of ECMO treatment, demonstrated that ECPR was successful for 934 out of 2236 neonatal and pediatric patients, with survival to discharge of 39% for neonates and 40% for children. Other retrospective, single-institution studies have shown survival rates as high as 72% to 80%.…”
Section: The Benefits Of Ecprmentioning
confidence: 99%
“…Although the return of spontaneous circulation is seen in 30 to 65% of pediatric patients following a cardiac arrest (more commonly found in-hospital cardiac arrest) long-term survival with good neurological recovery that may be achieved in only a minority [158][159][160]. Common causes of death in nonsurvivors are brain death or neurological futility, particularly among patients who have an out-of-hospital arrest [161].…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%
“…For the critical outcome of survival to hospital discharge, we identified very-low-quality evidence from 4 pediatric observational studies of IHCA [71][72][73][74] (downgraded for indirectness, inconsistency, and residual confounding) and very-low-quality evidence from 1 unpublished analysis of a study' s public dataset 75 (downgraded for serious risk of residual confounding) showing no benefit to the use of ECPR when compared with CPR without the use of ECMO (RR range, 0.64-1.63). We also identified low-quality evidence (downgraded for indirectness, inconsistency, and residual confounding) from a single pediatric study of IHCA 76 that showed benefit to ECPR when compared with CPR without the use of ECMO (OR, 2.5; 95% CI, 1.3-4.5; P50.007 in surgical cardiac diagnoses; OR, 3.8; 95% CI, 1.4-5.8; P50.011 in medical cardiac diagnoses).…”
Section: Consensus On Sciencementioning
confidence: 99%